The Study on the Impact of Using Supplementary Learning Materials for the Art Learning Area in the Subject of Western Music Education on the Learning Achievement of Grade 2 students at Ramkhamhaeng University Demonstration School (Elementary level) - Siengdee, Kittisak (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2025)
The purpose of this study was 1) to develop supplementary learning materials for the Art Learning Area in the subject of Western Music Education for Grade 2 students to meet the 80/80 efficiency criteria 2) to compare the learning achievement of Grade 2 students after learning with the supplementary learning materials in Western music education against the 70% standard and 3) to examine the satisfaction of Grade 2 students who learned with the supplementary learning materials in Western Music Education. This research is an experimental study. The sample used in the study consisted of 50 Grade 2 students from the Demonstration School of Ramkhamhaeng University (Elementary Level), selected using cluster random sampling. The data collection instruments included 1) supplementary learning materials for the Art Learning Area in the subject of Western Music Education 2) a lesson plan for Western Music Education 3) an academic achievement test for Western Music Education and 4) a student satisfaction questionnaire for Grade 2 students who used the supplementary learning materials. The data were analyzed using mean, standard deviation, percentage, and one-sample t-test. The research findings were as follows: 1) The instructional materials in Art (Western Music) had an efficiency of 88.56/82.27, which was higher than the 80/80 criterion 2) The students’ learning achievement was significantly higher than the 70 percent criterion at the .05 level and 3) Grade 2 students satisfaction with the use of the instructional materials was at the highest level.